An analysis to Section 10(2)(d) Competition Act 2010 in Malaysia - Tian, Joslyn Yeo Yi (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2022)
In Malaysia, Competition Act 2010 is an important act to promote economic development. It is implemented by promoting and protecting the competition process, thereby protecting the interests of consumers. The Act 2010 also prohibits abusive conduct of enterprise that is dominant in both of the goods or service markets. Section 10(2)(d) is discussed extensively in this article to clear people’s misconceptions that it only involves price discrimination. Therefore, this paper will identify the price discrimination and other conditions under the first limb; explain MyCC’s approach when dealing with abuse of a dominant position under the second limb; and highlight harm theory under the third limb. Data collection is done by referring to primary and secondary data. The findings show that the enterprises will perform price discrimination towards the customers by segregating customers into different groups. They are able to stop arbitrage between them and to control the price. Price discrimination as mentioned is happening in primary and secondary line and it includes rebate. In Malaysia, MyE.G. Services Berhad v MyE.G. Commerce Sdn.Bhd. case is a landmark case which shows how it harms competition in the downstream market. Furthermore, the paper found out that the MyCC uses effects-based approach by looking at the effects of the conduct on competition in the market to ensure good economic outcome consistent with the Act under the second limb. This means that it is considered to be an abuse if it harms consumers and exclude the competitors who are as efficient as the dominant enterprise. Moreover, the third limb is to be used by the victim who is not in a competitive relationship with the dominant firm. The differences and similarities are identified and comapred between the Act of Malaysia and the Treaty on the Functioning of the European Union. The article ends with recommendations to insert the terms “except in circumstances where public interest and public health would be affected” and enable MyCC to be an independent body. The paper concludes that price discrimination and other discriminations is decided by MyCC on a case-by-case basis. Section 10(2)(d) is referred when determining whether it is discriminatory towards existing and potential competitors that is no less efficient, and harms the competition process.